(untitled) (Panacea Journal of Medical Sciences, 2024)
Background: Poor psychological adjustment can have negative influence on health provider as well as patient care. Mentoring bears positive impact on mental health of medical students particularly in early stage of training. The study was conducted among first year MBBS students to assess the effect of structured mentorship programme on their psychosocial wellbeing. Materials and Methods: This was an interventional study, carried out at tertiary health care teaching institute in Mumbai City of Maharashtra, India. Psychological adjustment was evaluated using DASS (Depression, Anxiety, Stress Scale), General Self Efficacy Scale (GSES) and Scale of Psychological Wellbeing. Pre and post intervention scores were calculated. Data analysis was done by SPSS 20.0 and comparisons were performed by ‘Wilcoxon Signed Ranks Test’ and ‘Spearman’s rank correlation coefficient Test’. Results: A total of 62 (41.33%) students and 15 (100%) mentors participated in the study. There was statistically significant difference (p<0> Conclusions: The study reported improvement in psychosocial domains of medical students as a result of mentorship programme. Both students and mentors favored the programme and perceived several benefits.